The Rehnquist Court & Justice: An Oxymoron? - Erwin Chemerinsky (Washington University Journal of Law & Policy, 1999)
From the perspective of public interest law, the Rehnquist Court, simply put, is a disaster.
Keywords: Public interest law; United States. Supreme Court; William H. Rehnquist